2000
DOI: 10.1128/iai.68.3.1542-1548.2000
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Bacteria Express an Ulcerative Colitis pANCA-Related Protein Epitope

Abstract: Bacteria are a suspected pathogenic factor in inflammatory bowel disease, but the identity of the relevant microbial species remains unresolved. The pANCA autoantibody is associated with most cases of ulcerative colitis (UC) and hence reflects an immune response associated with the disease process. This study addresses the hypothesis that pANCA identifies an antigen(s) expressed by bacteria resident in the human colonic mucosa. Libraries of colonic bacteria were generated using aerobic and anaerobic microbiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(110 citation statements)
references
References 53 publications
3
103
0
4
Order By: Relevance
“…These trends are also observed in an independent analysis of the MetaHIT cohort (S11 Fig). research on separate cohorts also found that the community structure of biopsy-associated microbiomes [46][47][48] differed substantially between UC and CD patients, with UC appearing more like controls in the latter two; one study also saw similar trends in functional annotation from shallow shotgun sequencing [46]. UC and CD can also be differentiated serologically, with UC tending to be characterized more by autoantibodies directed at host neutrophils [49] [50], though these may arise through cross-reactivity with microbial proteins like OmpC [51], and CD being characterized more by antibodies against cell-surface glycans [52], Saccharomyces cerevisiae [50], and proteins such as flagellin [53]. This difference in the antigens associated with CD vs. UC may relate in part to biomolecules made and presented by the gut flora.…”
Section: Accurate Metagenome Annotation Clarifies Community Functionamentioning
confidence: 99%
“…These trends are also observed in an independent analysis of the MetaHIT cohort (S11 Fig). research on separate cohorts also found that the community structure of biopsy-associated microbiomes [46][47][48] differed substantially between UC and CD patients, with UC appearing more like controls in the latter two; one study also saw similar trends in functional annotation from shallow shotgun sequencing [46]. UC and CD can also be differentiated serologically, with UC tending to be characterized more by autoantibodies directed at host neutrophils [49] [50], though these may arise through cross-reactivity with microbial proteins like OmpC [51], and CD being characterized more by antibodies against cell-surface glycans [52], Saccharomyces cerevisiae [50], and proteins such as flagellin [53]. This difference in the antigens associated with CD vs. UC may relate in part to biomolecules made and presented by the gut flora.…”
Section: Accurate Metagenome Annotation Clarifies Community Functionamentioning
confidence: 99%
“…22, 23 While serum pANCA and ASCA are the best studied serologic markers for IBD, antibodies against the outer membrane porin C (anti-OmpC) of Escherichia coli and anti-CBir1 are also found in about 50 percent of patients with CD and to a lesser degree in UC patients. 24,25 The value of these disease markers in predicting CD development after IPAA has not been defined.…”
Section: Serologic Immune Markers Have Been Associated With Inflammatmentioning
confidence: 99%
“…The pANCA (perinuclear antineutrophil cytoplasmic antibody) autoantibody, which is di-rected against neutrophil proteins, cross-reacted with a microbial antigen epitope in E. coli and Bacteroides (64). In E. coli, the epitope was located on the OmpC protein, one of the well-characterized porin proteins.…”
Section: Infections In Adultsmentioning
confidence: 99%